Notice of Removal: Impedance matrix approach to stochastic assessment for balanced and unbalanced voltage sags on transmission networks - Gopi R.J.; Ramachandaramurthy V.K.; Au M.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Stochastic assessment is a method to predict the severity and number of voltage sags at a bus of interest in the transmission network system. In this paper, an analytical technique using impedance matrix is developed to predict the voltage magnitudes due to balanced and unbalanced faults at unlimited buses in an electrical network. The proposed technique was applied to an IEEE 24-buses electrical network to illustrate its application. The results show that the proposed technique is able to predict the voltage magnitude at any buses and the number of sags per year.